Faktor yang mempengaruhi sikap pengguna terhadap pemasaran media sosial - Ami Joselina, Abu Bakar (2018)
The purpose of this study is to examine the about factors that influence the attitude of the consumers about marketing through the social media. These factors are reliability on information, privacy concerns, the perceptual reliability on online advertising and the security control against social media. This research involved students from School of Business Management, College of Business Universiti Utara Malaysia. A total of 340 questionnaires were distributed and 315 questionnaires were returned and used for analysis. In this study, correlation and regression analysis has been used to analyze the data using SPSS version 21.0. The findings showed that there is a significant relationship between reliability on information, privacy concerns, and the perceptual reliability on online advertising and the security control on attitude of consumers towards marketing on social media. In addition, it was found that security control has the strongest influence on consumers’ attitude towards marketing on social media. As a conclusion, social media is one of the marketing methods that is effective but the management of social media marketing should implement it effectively and meticulously.